Analisa Fundamental Makro, Struktur Modal, Struktur Kepemilikan, Kinerja Keuangan, Karakteristik Perusahaan Terhadap Nilai Perusahaan dengan GCG Sebagai Variabel Moderasi pada Sub Sektor Perusahaan Logam yang terdaftar di BEI - Erdiana, Della; Hwihanus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to examine the influence of factors such as macroeconomic conditions, capital structure, ownership structure, financial performance and company characteristics on company value in the context of metal companies in Indonesia. Good Corporate Governance (GCG) is also included as a moderating variable. Through a quantitative approach, this research provides in-depth insight into the factors that influence company value, with the hope that the results can provide guidance for corporate decision makers, regulators, investors and researchers to increase the value of metal companies in the Indonesian capital market. A good company value assessment is reflected in the high share price, which is a positive signal for potential investors. Good Corporate Governance (GCG) is considered a structure that regulates relationships between various parties in a company. The research hypothesis shows that factors such as Macro Fundamentals, Capital Structure, Ownership Structure, Financial Performance and Company Characteristics can influence Company Value. The research method used is descriptive with a quantitative approach. The test results show that not all factors have a significant influence on Company Value.